Studi Keterdapatan Torium Pada Endapan Laterit Bauksit di Pulau Singkep Dalam Rangka Pengembangan Eksplorasi Torium di Wilayah Granit Jalur Timah - Ngadenin; Widana, Kurnia Setiawan; Karunianto, Adhika Junara (BRIN Publishing, 2018)
The thorium exploration in the last five years in the granite tin belt region is targeted at thorium availability in primary and secondary tin deposits. Singkep island is the part of granite tin belt which potential for thorium occurences either primer or secondary deposits. The purpose of this study was to determine the characteristics of thorium availability in bauxite laterite deposits concerning thorium content and its relation to the availability of radioactive minerals and cerium (Ce), lanthanum (La), Yttrium (Y), and zircon (Zr) contents on the bauxite laterite deposit. The data obtained from this study will be used as an evaluation material for the development of thorium exploration in bauxite laterite deposits in Indonesia. The methods used are geological mapping, thorium concentration measurements, and sampling of pan concentrate for mineral grain analysis and analysis of Ce, La, Y, and Zr contens. The lithology of the study area was granite that had weathered and turned into bauxite laterite deposit with thorium content ranging from 25.9 to 177.8 ppm eTh. The concentrate of the repeating result is zircon-ilmenite concentrate with radioactive mineral content composed of zircon, monazite, and anatase. La concentration on zircon-ilmenite concentrate is 0–412 ppm, Ce is 0–80 ppm, Y is 27–82 ppm and zircon is 9,420–100,000 ppm. Avaibility of thorium at the bauxite laterite deposit on Singkep Island is closely related to the zircon, monazite, and anatase minerals. Characteristics of thorium availability in the bauxite laterite deposit are similar to the thorium characteristics of the primary and secondary tin deposits.